2005
DOI: 10.1002/jcb.20678
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib, a selective EGFR tyrosine kinase inhibitor, induces apoptosis through activation of Bax in human gallbladder adenocarcinoma cells

Abstract: Although gefitinib, a selective inhibitor of epidermal growth factor receptor (EGFR) tyrosine kinase, has been clinically demonstrated to be effective for certain cancer cell types, the molecular mechanisms of the anti-tumor activity have not been fully elucidated. In this study, we investigated the mechanism of gefitinib-induced growth inhibition and apoptosis in HAG-1 human gallbladder adenocarcinoma cells. Treatment of gefitinib at a dose of 1 microM resulted in a significant growth inhibition, and the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…Interestingly, the EGFR-TKI erlotinib was found to up-regulate EGFR in HuCCT1 cholangiocarcinoma cells, but combined treatment with the anti-EGFR antibody cetuximab or blockage of erlotinib-induced EGFR synthesis by a small interfering RNA abrogated this TKI effect, and resulted in an inhibition of cell proliferation and increased apoptosis in the HuCCT1 cells [178] . Moreover, in this study, cetuximab was shown to be equally effective when administered alone or in combination with erlotinib in partially suppressing Gefitinib EGFR Cell culture HAG-1 human gallbladder adenocarcinoma cell line Dose-dependent in vitro cell growth inhibition by arresting cells in G0/G1, followed by progressive cell apoptosis; inhibition of EGFR phosphorylation and of Erk1/2 and Akt activation; decreased cyclin D1 mRNA and induced accumulation of p27 protein, a negative cell cycle regulator [176] Gefitinib…”
Section: Cholangiocarcinoma Cellsmentioning
confidence: 66%
See 1 more Smart Citation
“…Interestingly, the EGFR-TKI erlotinib was found to up-regulate EGFR in HuCCT1 cholangiocarcinoma cells, but combined treatment with the anti-EGFR antibody cetuximab or blockage of erlotinib-induced EGFR synthesis by a small interfering RNA abrogated this TKI effect, and resulted in an inhibition of cell proliferation and increased apoptosis in the HuCCT1 cells [178] . Moreover, in this study, cetuximab was shown to be equally effective when administered alone or in combination with erlotinib in partially suppressing Gefitinib EGFR Cell culture HAG-1 human gallbladder adenocarcinoma cell line Dose-dependent in vitro cell growth inhibition by arresting cells in G0/G1, followed by progressive cell apoptosis; inhibition of EGFR phosphorylation and of Erk1/2 and Akt activation; decreased cyclin D1 mRNA and induced accumulation of p27 protein, a negative cell cycle regulator [176] Gefitinib…”
Section: Cholangiocarcinoma Cellsmentioning
confidence: 66%
“…However, gefitinib given in combination with the MEK inhibitor CI-1040 was associated with a profound inhibition of HuCCT1 tumor growth that appeared to be linked to either a greater p42/44 MAP kinase inhibition or to simultaneous inhibition of Akt and p42/44 MAPK signaling [179] . In comparison, gefitinib alone suppressed both the autophosphorylation of p42/44 MAPK and to a lesser degree that of Akt in the HAG1 human gallbladder carcinoma cell line [176] . Interestingly, the EGFR-TKI erlotinib was found to up-regulate EGFR in HuCCT1 cholangiocarcinoma cells, but combined treatment with the anti-EGFR antibody cetuximab or blockage of erlotinib-induced EGFR synthesis by a small interfering RNA abrogated this TKI effect, and resulted in an inhibition of cell proliferation and increased apoptosis in the HuCCT1 cells [178] .…”
Section: Cholangiocarcinoma Cellsmentioning
confidence: 87%
“…23) When the TfR/EGFR recycling pathways were disrupted by the TfR/EGFR antibody, certain compounds, or other processes, apoptosis was triggered. [24][25][26] These results explain to some extent why increased CHMP6 can induce apoptosis. Whether the oncosis induced by CHMP6 overexpression is related to disrupted TfR/EGFR recycling requires further investigation.…”
Section: Discussionmentioning
confidence: 82%
“…Treatment of lung tumors with the TKI gefitinib down-regulates the PI(3)K/Akt pathway, leading to decreased cell proliferation and programmed cell death [187][188][189]. An increasing body of evidence highlights the central role of ErbB3 in the circuitries that mediate resistance to TKIs.…”
Section: Resistance To Targeted Therapymentioning
confidence: 99%